2000
DOI: 10.1007/s004250000335
|View full text |Cite
|
Sign up to set email alerts
|

Fructan accumulation induced by nitrogen deficiency in barley leaves correlates with the level of sucrose:fructan 6-fructosyltransferase mRNA

Abstract: Hydroponically cultivated barley plants were exposed to nitrogen (N)-deficiency followed by N-resupply. Metabolic and genetic regulation of fructan accumulation in the leaves were investigated. Fructan accumulated in barley leaves under N-deficiency was mobilized during N-resupply. The enhanced total activity of fructan-synthesizing enzymes, sucrose:sucrose 1-fructosyltransferase (EC 2.4.1.99) and sucrose:fructan 6-fructosyltransferase (6-SFT; EC 2.4. 1.10) caused by N-deficiency decreased with the mobilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 31 publications
7
38
0
5
Order By: Relevance
“…Therefore, although SST and FFT activities were not evaluated in the present study, the higher fructan concentration found in N-limited plants could be associated with increases in the activity of these enzymes, as reported by Wang et al (2000) for 6-SFT in barley leaves. Since sucrose is the precursor molecule in the biosynthesis of fructans, the metabolism of these two compounds is closely related.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, although SST and FFT activities were not evaluated in the present study, the higher fructan concentration found in N-limited plants could be associated with increases in the activity of these enzymes, as reported by Wang et al (2000) for 6-SFT in barley leaves. Since sucrose is the precursor molecule in the biosynthesis of fructans, the metabolism of these two compounds is closely related.…”
Section: Discussionmentioning
confidence: 66%
“…Fructan biosynthesis is initiated by the enzyme sucrose:sucrose 1-fructosyltransferase (1-SST), which catalyses the formation of 1-kestose from sucrose (Vijn et al, 1998). It has been reported that 1-SST was induced by high sucrose contents in barley leaves (Muller et al, 2000;Wang et al, 2000). These indicate that the enzyme genes which catalyze sucrose biosynthesis are also important for fructan productions.…”
Section: Discussionmentioning
confidence: 99%
“…(Amiard et al, 2003;Wang et al, 2003). A detailed fructan analysis in both Clipper and Sahara leaves may clarify whether these compounds have any direct involvement in B tolerance.…”
Section: Metabolite Profiling Of Barley In Response Tomentioning
confidence: 99%